The crime of Galileo - De Santillana, George 1902- (Chicago, Illinois University of Chicago Press, 1955)
Galileo's scientific work which led him into a quarrel with the church.
The days of discovery -- "Domini canes" -- Philosophical intermezzo -- Saint Robert Bellarmine -- The decree -- Bellarmine's audience -- The years of silence -- Urban VIII -- The "Dialogue" -- The summons -- The inquisitors' plight -- The trial -- The problem of the false injunction -- Change of course -- The sentence -- Aftermath.
Includes bibliographical references and index.
Keywords: Galilei, Galileo -- 1564-1642.